Studi Kerusakan Hutan Mangrove di Desa Lewolaga, Kecamatan Titehena, Kabupaten Flores Timur, Provinsi Nusa Tenggara Timur - Dominikus Vorel Friski Beribe; Ludji Michael Riwu Kaho; Astin E. Mau (Program Studi Kehutanan, Fakultas Pertanian, Universitas Nusa Cendana, 2025)
Mangrove forest is a forest that grows along the coast which is very beneficial. However, the condition of mangroves, both qualitatively and quantitatively, keep dropping from year to year which causes damage to mangrove forests in Indonesia.One of them is happened to the Mangrove Forest in Lewolaga Village, Titehena District, which tends to experience a reduction in area because many are converted into settlements, become boat moorings, and logging by the community for various purposes. This study aims to determine the forms of damage that occurs and the level of diversity of mangrove-type vegetation as evidence of forest damage in Lewolaga Village, Titehena District, East Flores Regency, East Nusa Tenggara Province. This research lasted for one month, namely in September 2022 in Lewolaga Village, Titehena District, East Flores Regency. There were 7 respondents who were interviewed who were obtained using a non-probability sampling method, namely snowball sampling and analyzed using a qualitative descriptive analysis method and vegetation analysis with a sampling intensity of 10% and an area of 5.89 ha of mangrove forest. The results showed that 1) Mangrove forest damage in Lewolaga Village was caused by human activities, namely (a) making boat moorings and boat crossings by clearing land, (b) salt ponds and fish ponds, ( c) utilization of mangroves for making turo, (d) during the dry season, people in Lewolaga Village utilize mangroves by cutting mangrove leaves to make goat food, and others. 2) the species diversity index was classified as medium with an H' value at the seedling level of 1.15, at the sapling level of 1.17, at the pole level of 1.24 and at the tree level of 1.19. While the diversity of species at all levels indicates disturbance and pressure by external factors that cause damage to mangrove forest vegetation.